Calcite accumulation in a South African heuweltjie: Role of the termite Microhodotermes viator and oribatid mites. (November 2019) - Francis, Michele Louise; Poch, Rosa M.
Abstract: The aim of the study was to understand calcium and organic matter cycling in a calcareous heuweltjie mound in Papendorp, inhabited by the termite Microhodotermes viator. We used micro-FTIR and Alizarin red staining techniques on soil micromorphology thin sections and compared these to non-calcareous M. viator excrement from a non-calcareous mound in Stellenbosch. The non-calcareous M. viator excrement was a source of lignin, cellulose and localised calcium oxalate. This suggests that the oxalate-carbonate pathway is likely to operate or have operated in the past in soils with an accumulation of termite excrement. In the calcareous Papendorp heuweltjie, phytoliths, amorphous organic material lining the termite tunnels and excrement from secondary decomposers (oribatids) were associated with elevated calcite concentrations and showed few lignin and cellulose micro-FTIR peaks. Our study suggests the primary role of M. viator is accumulating calcium- and/or oxalate-rich plant materials and introduces the importance of mites in further processing this material. The termites do not appear to biomineralize the calcite directly. Abiotic dissolution-reprecipitation appears to have been a volumetrically important process in the closing of the pores and development of the petrocalcic horizon in the Papendorp heuweltjie into its present form. Graphical abstract: Calcified oribatid excrements in the Papendorp heuweltjie petrocalcic horizon with a higher concentration of calcite than the surrounding micromass (arrowed). Thin section, cross-polarized light. Image 1 Highlights: Calcium oxalate present in Microhodotermes viator termite excrement. Oribatid activity evident in the heuweltjie. Calcite associated with amorphous organic tunnel linings. Calcite dissolution-reprecipitation evident in heuweltjie.